Orchid Identification and Collection Techniques in the Kembang Kuning Resort Area, Rinjani Mount National Park (RMNP) - Suripto; Yayat Maulidan (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
The Rinjani Mount National Park (RMNP) area is one part of the tropical rain forest in the West Nusa Tenggara region. Orchid is one of the flora that has a high bioprospective in this area. The spread of natural orchids can continue to grow and there are still many that have not been identified. This study aims to train specific techniques in collecting and identifying natural orchids at The Resort of Kembang Kuning, Rinjani Mount National Park. The collection of orchids was carried out using the roaming method, while the identification of orchid species was carried out using a species determination technique through observation of morphological and anatomical descriptions. The out comes of this study are an increase in participants' appreciation, knowledge and skills in collecting and identifying species of natural orchids in the Kembang Kuning area of Rinjani ​​Mount National Park. Based on the observations obtained 9 species (7 species were identified to the species level and 2 species were identified to the genus level) from 6 genera of natural orchids in area of The Kembang Kuning Resort, The Rinjani Mount National Park (RMNP).